Academic Self-Efficacy as the Mediator of Adolescent-Parent Secure Attachment Effect towards the Academic Stress of Senior High School Students - Putri, Erika Kusuma; Febriani, Arum (Jurnal Psikologi, 2021)
This study aimed at examining the role of academic self-efficacy as a mediator of adolescent-parent secure attachment effect towards academic stress of senior high school students. The hypothesis of this study was the adolescent-parent secure attachment effect towards the academic stress of senior high school students is mediated by the academic self-efficacy. Two hundred sixty four 11thgrade senior high school students from three different schools in Yogyakarta were recruited as the research participants. Data collection exerted the adolescent-parent attachment scale, academic stress scale, and academic self-efficacy scale. Mediation analysis was conducted by using the conditional process modelling. Result showed that the adolescent-parent secure attachment affected academic stress of senior high school students is mediated by the academic self-efficacy with an indirect effect coefficient of -0,199. The importance of the role of academic self-efficacy in reducing academic stress among students is discussed. The results of this study are expected to serve as evaluation materials for parents to understand that the success of teenagers in school is not only the responsibility of the teachers and the school. Future researchers could also add a variable of adolescent-peers attachment to expand more knowledge on the topic.